Proteomic and N-glycosylation analysis of fertile egg white during storage and incubation in chickens - Daqing Dai; Xiqiong Wang; Kexin Wu; Fangren Lan; Jiaming Jin; Wenxin Zhang; Chaoliang Wen; Junying Li; Ning Yang; Congjiao Sun (Poultry Science)
Proteins in egg whites play vital roles in embryonic development. Simultaneously, protein modification is affected by the surrounding environment, which ultimately affects the structure and function of proteins. Here, we measured the phenotypes of eggs at different time points during storage and incubation and used 4D label-free quantitative proteomics technology and liquid chromatography/tandem mass spectrometry (LC-MS/MS)-technique to identify the differential proteins and N-glycosylation sites in egg whites during storage and incubation. We found that the differential N-glycoproteins in the early stage of storage were mainly related to protein structure changes, antibacterial activity, and cell proliferation, and that there were more protease inhibitors in egg whites, which decreased in the later stage of storage. Finally, eleven possible protein markers and N-glycosylation sites were identified to significantly change during storage and may exert an effect on hatchability, including the proteins involved in antibacterial activity (OVOA-N855, CLU-N154, ogchi-N82, PIGR-N290, WFDC2-N120), protein structure (LOC776816), and cell proliferation (ASAH1-N173). This study provides substantial insights into the physical and molecular compositional changes in egg whites under different storage times and revealed their potential effect on chick embryo development.